PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATERI SKETSA DAN ILUSTRASI - Iswani, Yuni; Mulyono, Heri; Devegi, Mourend (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
The purpose of this study is to produce valid android-based learning media on sketch and illustration material for class X DKV. To produce practical android-based learning media on sketch and illustration material for class X DKV. This research method uses the Research and Development (R&D) method with the ADDIE development model. The subjects of this study consisted of 3 media validation people, 3 material validity people, 1 teacher practicality person and 32 student practicality people. The results of this study show the average value of the media validation test by the validator is 88.03% with a very valid category while the material validation is 97.69% with a very valid category. The teacher practicality test is 98.33% with a very practical category While the student practicality is obtained at 93.23% with a very practical category. Android-based learning media is suitable for use as a learning medium. improving the quality of learning, with the use of more interactive and efficient media for teachers and students, and is able to reach more students in areas that are difficult to access.